China’s Belt-and-Road Initiative: Future Bonanza or Nightmare? - Lim, Linda (2018)
Despite its growing prominence internationally, China’s Belt-and-Road Initiative (BRI) is facing a host of challenges. Unless these are addressed, Beijing will find the BRI ending up more a nightmare than a bonanza.